Earth, air lime and natural hydraulic lime mortars - Santos, Tânia (2021)
Rendering and plastering mortars supply protection to buildings and may contribute significantly to thermal and acoustic comfort of the indoor environmental. Being protective layers, they suffer aging and use and have to be repaired and sometimes replaced. Taking this into account, rendering and plastering mortars must comply with technical, but also ecological requirements. Therefore, it is essential to use more recycled and low embodied energy materials to produce mortars, to lower their environmental impact. In the present study five different mortars with different binders and aggregates were produced and characterized. The analysed mortars are: an earth mortar (E); an air lime mortar (CL); an air lime mortar with brick waste instead of sand (CL_BW); an air lime-brick dust mortar (CL+BD); and a natural hydraulic lime mortar (NHL). Except the CL_BW, all the mortars were produced with a river sand. The mortars were tested for wet bulk density, flow table consistency, drying shrinkage, colour, dry bulk density, dynamic modulus of elasticity, flexural and compressive strength. The E and CL mortars present similar flexural and compressive strengths, although the CL mortar was produced with an excess of water, like what happens on site when air lime mortar is produced by professionals only skilled to cementitious ortars. The use of brick waste and dust in all the air lime mortar promotes an increase of the dynamic modulus of elasticity, flexural and compressive strength, except for the CL_BW mortar that presents a flexural strength similar to the CL mortar. The bulk density of the latter is very low in comparison with all the other sandy mortars. NHL mortar presents a slightly higher strength.